Analisis Atribut Kepentingan Dan Kinerja Pelayanan Dijou Coffeebar Dan Café Kiyo Di Bandar Lampung - Jenesya Afgiani Reza; Agus Hudoyo; Achdiansyah Soelaiman (Politeknik Negeri Lampung, 2022)
Coffee consumption has now become a lifestyle, especially among the younger generation. This can be seen from the number of coffee shop businesses. More and more coffee shopbusinesses make competition tougher. There are many ways that can be done to maintain theexistence of coffee shops, one of which is by improving the quality of service. This researchaims to identify service attributes that are considered important and satisfy consumers andservice attributes need to be maintained and improved by coffee shops. Samples were takenfrom the population of coffee shop visitors who were selected in stages by drawing tablenumbers. The number of samples as many as 70 respondents spread over the two coffee shops.Data collection was carried out from August to September 2020. Questionnaire scores wereanalyzed using validity and reliability tests.The analytical method used is ImportancePerformance Analysis (IPA). The results showed that the service attributes consideredimportant by Dijou Coffeebar consumers were 17 attributes, Café Kiyo 18 attributes.Attributes whose performance was considered satisfactory by Dijou Coffeebar consumerswere 12 attributes, Café Kiyo 16 attributes. Attributes whose performance quality must bemaintained Dijou Coffeebar and Café Kiyo have several similarities, taste, price, tasteconsistency, accuracy in recording menus, security, product guarantees, cleanliness,employee courtesy, ease of payment, convenience of place and availability of tables & chairs.A different attribute at Dijou Coffeebar is the availability of parking spaces. At Café Kiyo,menu variations, speed of service, concern for customers, responsiveness to criticism &suggestions and the availability of parking spaces. Attributes whose performance qualityneeds to be improved at Dijou Coffeebar are speed of service, concern for customers,responsiveness to criticism and suggestions, availability of toilets and wifi. At Café Kiyo,availability of wifi and parking spaces.